Factors influencing disaster response behavior of international tourists under the Tokyo Metropolitan Earthquake scenario - Choi, Sunkyung; Yoshida, Kozo; Yamaji, Hideyuki; Shindo, Hiroaki; Maharjan, Rajali (Frontiers in Sustainable Tourism, 2023)
As Japan continues to become a popular global tourism destination, its vulnerability to disasters cannot be overlooked. Although the Japanese government has implemented different disaster prevention policies and practices, there is a lack of investigation into disaster response behaviors, such as information seeking, evacuation, and the factors affecting these. This study clarified the factors influencing the disaster response behavior of international tourists in the context of the anticipated Tokyo Metropolitan Earthquake scenario. A questionnaire survey was conducted, and the logistic regression model was used to understand the causative factors. The results revealed that the variable knowledge on disaster response behavior in earthquakes influences individuals' evacuation decisions, especially when people choose to follow others. These findings will be beneficial for tourism stakeholders and policymakers to establish effective tourism crisis management planning, including information provision, shelter allocation, and collaborative initiatives.